Effect of Mercury concentration on P. putida growth in Mercury removal - Abdul Aziz, Mohd Azoddein; R. M., Yunus; Nik Meriam, Nik Sulaiman; Ahmad Bazli, Bustary; Faten Ahada, Mohd Azli; Suzana, Che Sayuti (TAF Publishing, 2017)
Mercury is a toxic pollutant emitted from industrial sectors to the environment and distributed globally. The potential for biological treatment of industrial wastewater contaminated with mercury was evaluated using Pseudomonas putida (P. putida) under various conditions in a bioreactor. The effect of mercury concentration on the P. putida growth of bacteria and also mercury removal was determined. Modiβications in optimum operating conditions in shake βlask and bioreactor need to be determined so it could bring us to a better result. In this research, optimum conditions for growth of P. putida in shake βlask are identiβied: acclimatization time 24 hours, orbital shaker speed 180rpm, temperature 37°C, pH 7, and nutrient concentration 8g/L. The removal efβiciency obtained is 99% for 1ppb, 99.8% for 6ppb, and 98.6% for 19ppb while for 1000ppb mercury, the removal efβiciency is 92% for 1 hour and 98% for 28 hours. In 2L bioreactor, same condition as shake βlask is applied with agitator speed of 180 rpm and aeration time of 0.50vvm. For 1300ppb and 3000ppb, the removal efβiciency is 89% and 94%, respectively. The βindings of this study can be used as a reference for future application in industrial wastewater treatment plant.